2003
DOI: 10.1097/01.prs.0000049448.56511.23
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Sparing Latissimus Dorsi Myocutaneous Flap with Maintenance of Muscle Innervation, Function, and Aesthetic Appearance of the Donor Site

Abstract: In this report, the authors describe the application of a muscle-sparing technique to harvest a myocutaneous latissimus dorsi muscle flap, including only a tiny lateral muscle segment but carrying a large skin paddle, with the advantage of leaving intact innervation and function of the remaining latissimus dorsi muscle. According to the experiences and complications associated with the pure thoracodorsal artery perforator harvest at the authors' institution, the necessity of increasing the reliability of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 10 publications
0
49
0
3
Order By: Relevance
“…9 The advantages of being able to split the muscle in a medial and lateral flap are that only the lateral part of the muscle can be harvested leaving the medial flap in situ, providing strength in the donor limb, benefitting certain patients, or that the flap is used for two transfers. 10 For innervated functional muscle transplant procedures, however, it is essential to have knowledge about the length of the nerve pedicles available to each of the segments of the latissimus dorsi muscle to preoperatively plan the donor nerve. It was previously described that 3 cm of nerve was essential, but with current microsurgical techniques, 1 cm is sufficient.…”
mentioning
confidence: 99%
“…9 The advantages of being able to split the muscle in a medial and lateral flap are that only the lateral part of the muscle can be harvested leaving the medial flap in situ, providing strength in the donor limb, benefitting certain patients, or that the flap is used for two transfers. 10 For innervated functional muscle transplant procedures, however, it is essential to have knowledge about the length of the nerve pedicles available to each of the segments of the latissimus dorsi muscle to preoperatively plan the donor nerve. It was previously described that 3 cm of nerve was essential, but with current microsurgical techniques, 1 cm is sufficient.…”
mentioning
confidence: 99%
“…Schwabegger et al 7 suggested a longer and narrower muscle portion which was 4 to 8 cm in length and 2 cm in width to be harvested with the flap. However, they did not clarify the intramuscular branching, course, and surgical dissection of the thoracodorsal neurovascular pedicle, whereas preserving of the descending and transverse branches of the thoracodorsal vessels and nerve in an opposite fashion to each others was the most important step of the dissection in our technique.…”
Section: Discussionmentioning
confidence: 99%
“…Schwabegger et al 7 first introduced the ''muscle sparing LD flap" concept with a series of 7 cases in 2003. Recently, the flaps with some modifications have been used as pedicled regional flaps for postmastectomy breast reconstructions.…”
mentioning
confidence: 99%
“…Eventually, efforts were made to reduce donor-site morbidity by the introduction of the TDAP flap5 and the muscle-sparing LD flap,6 in which the muscle is totally or partially spared, avoiding all the complications related to its sacrifice 11…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1980s, Tobin et al 4 was the first to introduce the concept of splitting the LD muscle and this was the basis for the development of the thoracodorsal artery perforator (TDAP) flap and eventually the muscle-sparing LD (MS-LD) 5 6…”
Section: Introductionmentioning
confidence: 99%